Successful application of high-flow nasal cannula in a patient with postoperative respiratory disturbance after bilateral sagittal split ramus osteotomy surgery - A case report - Jung, Ki Tae; Ji, In Gook; Kim, Sang Hun (Anesthesia and pain medicine (Korean society of anesthesiologists), 2018)
Bilateral sagittal split ramus osteotomy (BSSRO) is generally indicated for mandibular setback, to improve occlusion, masticatory function, and aesthetics by altering the mandibular position. However, BSSRO narrows the pharyngeal airway and increases airway resistance, resulting in postoperative respiratory disturbances during emergence from anesthesia. Oxygen delivery system via high-flow nasal cannula (HFNC) has been known to improve airway patency and oxygenation via low-level positive pressure as well as reduce the respiratory load. We report a case of postoperative respiratory disturbance, following a large mandibular setback, despite nasotracheal extubation in the fully awake patient. Respiratory disturbance was successfully controlled after oxygen delivery via HFNC until self-respiration was completely restored. Therefore, the use of HFNC may facilitate the control of postoperative respiratory disturbances induced by anatomical changes in upper airway after BSSRO surgery. KCI Citation Count: 0